Using Google Sites as Science Learning Media to Increase Elementary School Student Creativity - Agustina, Shintia Dwi; Shidiq, Galih Albarra; Kholik, Nur (DAS Institute, 2023)
People have to be creative to survive and compete in the 21st century. Creativity can be developed through the learning process in schools. The learning process using interesting media can accelerate the development of creativity. This study aims to determine the use of google sites to increase elementary school students' creativity in learning natural sciences (IPA). This research is qualitative research with descriptive analysis techniques with library research that tries to describe existing phenomena which happen now or in the past. This research shows that learning using Google sites as learning media can have a good impact on student creativity. Students can be facilitated and the website can also be used to get a variety of knowledge. The condition is suitable for the demands of 21st-century skills. In conclusion, Google Sites is suitable and appropriate for use in the learning process. With Google Sites learning media, students can be more creative and can play an active role in the learning process in class.